From Grievance to Welfare: Reshaping the Identity of Past Gross Violation of Human Rights Victims in Indonesia - Harison Citrawan (LIPI Press, 2018)
This article attempts to describe a shift of identity amongst the victims and survivors of past gross human rights violations in Indonesia, through examining the economic violence of past gross human rights violations in the country and the current available reparative mechanisms Arguably through this examination, and given a wider framework of Indonesia’s transition policy, it could be seen that there is a reshaping of victim’s interest from state’s violence grievances to structural economic vulnerability. This shift is mainly caused by several contributing factors: first is the absence of national level holistic paradigm in resolving the past. This could be depicted in the absence of clear legal framework and the lack of political will to resolve the past; and second is the emerging pragmatic choice made by the government and the (group of) victims/survivors- particularly given the current existing challenge of welfare-based needs faced by the victims/survivors. While the exercised reparative mechanisms- through judicial process and general assistance programs have been considerably useful in empowering the victims/survivors, this situation would potentially fail to portrait the structural (economic) violence that happened in the past.